(untitled) - FAO (Rome, 2000)
Information on wild relatives of dometic animal genetic resources is also provided. The diversity represented in wild relatives has the potential to make important contributions to food and agricultural production. This edition of the WWL-DAD also includes a section on the potential costs and benefits of feral animal populations of animal genetic resources.
Keywords: animal breeding,animal genetics